The typology of phraseological units with faunic component (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the problem of forming typology of phraseological units with faunic component in the Ukrainian language based within an ethnic and cultural group of stable language structures each of which owing to special inner form is connected to discursively stereotypical communicative and pragmatic situation
Keywords: fauneme; phraseological unit; partonimе; animalism